1982
DOI: 10.21236/ada118925
|View full text |Cite
|
Sign up to set email alerts
|

Basic Research on Oxynitride Glasses.

Abstract: BEFORE COMPLE'TING FORM I. REPORT NUMBER 12. GOVT ACCESSION NO 3.,AECIPIENT'S CATALOG NUMUE 4. TITLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The 15 weight percent samples were nearly all crystalline and microhardness values were relatively low. These data correlate well with previous findings[12,25,26] and support the theory that the substitution of nitrogen for oxygen in the glass structure increases the number of bridging bonds in the glass network, causing greater stiffness. Microhardness data as a function of nitrogen content are displayed inFigure 9.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The 15 weight percent samples were nearly all crystalline and microhardness values were relatively low. These data correlate well with previous findings[12,25,26] and support the theory that the substitution of nitrogen for oxygen in the glass structure increases the number of bridging bonds in the glass network, causing greater stiffness. Microhardness data as a function of nitrogen content are displayed inFigure 9.…”
supporting
confidence: 91%
“…In the • oxynitride glass structures, nitrogen in the trivalent state is thought to replace divalent oxygen. The resultant nitrogen bridging forms three bonds, potentially increasing the crosslinking in the glass network [12]. It was shown that as nitrogen content increases glass properties improve; -specifically, increased viscosity, higher glass transition temperature, increased hardness, and decreased coefficient of thermal expansion [13].…”
Section: Introductionmentioning
confidence: 99%